2017
DOI: 10.1086/689744
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormones Reduce Incubation Period without Developmental or Metabolic Costs in Murray River Short-Necked Turtles (Emydura macquarii)

Abstract: Metabolic processes are affected by both temperature and thyroid hormones in ectothermic vertebrates. Temperature is the major determinant of incubation length in oviparous vertebrates, but turtles can also alter developmental rate independent of temperature. Temperature gradients within natural nests cause different developmental rates of turtle embryos within nests. Despite temperature-induced reductions in developmental rate, cooler-incubated neonates often hatch synchronously with warmer siblings via metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 94 publications
2
16
0
Order By: Relevance
“…However, adaptation may also fashion canalized responses; for example, eggs of cool‐climate populations of Lacerta agilis hatch after shorter incubation periods than do those of warm‐climate conspecifics, even at the same egg size (Rykena, ). The mechanism remains unknown, but recent experimental studies on turtles show that maternal allocation of thyroid hormones in egg yolk can accelerate development (and thus, hasten hatching) without any major impact on hatchling phenotypes (McGlashan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, adaptation may also fashion canalized responses; for example, eggs of cool‐climate populations of Lacerta agilis hatch after shorter incubation periods than do those of warm‐climate conspecifics, even at the same egg size (Rykena, ). The mechanism remains unknown, but recent experimental studies on turtles show that maternal allocation of thyroid hormones in egg yolk can accelerate development (and thus, hasten hatching) without any major impact on hatchling phenotypes (McGlashan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Of particular interest are the physiological mechanisms and endocrine responses, such as how hormones might alter development and behavior. Thyroid hormones can induce changes to metabolism or hatching behavior independent of temperature without any metabolic or post‐hatching cost (McGlashan, Thompson, Van Dyke, & Spencer, ; O'Steen & Janzen, ). Increased thyroid hormone concentrations strongly correlate with the final stages of embryogenesis (Dimond, ; Shepherdley et al, ) and could be important for hatching behavior (McGlashan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although temperature is a major determinant of the rate of embryonic development in ectotherms (Booth, 1998;Deeming & Ferguson, 1991;Monaghan, 2008), hatching time is nonetheless plastic (Doody, 2011;Packard & Packard, 2000;Spencer & Janzen, 2011;Warkentin, 2011 Thompson, Van Dyke, & Spencer, 2017;O'Steen & Janzen, 1999). Increased thyroid hormone concentrations strongly correlate with the final stages of embryogenesis (Dimond, 1954;Shepherdley et al, 2002) and could be important for hatching behavior (McGlashan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in some reptile species, variation in nest temperatures could cause intraclutch variation in developmental speed, but hatching asynchrony is seldom reported. THs are suspected to play a role in metabolic compensation, which leads to synchronous hatching (McGlashan et al 2017). Such studies never measured THs levels in unincubated eggs and did not try to separate the roles of maternally derived THs and endogenously produced THs before hatching.…”
Section: Ecological Sources Of Variation In Maternal Ths In Reptiles Andmentioning
confidence: 99%
“…In a few recent studies, THs were injected into eggs at later embryonic stages beyond naturally occurring levels. They showed that elevated egg THs can speed up prenatal development, increase heart rate (proxy of metabolic rate), and early posthatching growth in turtles (Sun et al 2016;McGlashan et al 2017). Furthermore, such treatments also decreased the expression of the androgen-converting enzyme aromatase and levels of estradiol and sex ratio (Sun et al 2016), suggesting complex interactions among different groups of hormones.…”
Section: Effects Of Maternal Ths On Reptiles and Amphibiansmentioning
confidence: 99%